BSCI-06. FREQUENCY OF BRAIN METASTASIS FROM BREAST AND LUNG CANCER IN THE UNITED STATES -- A POPULATION-BASED ASSESSMENT - Ostrom, Quinn (Neurooncol Adv, 2019)
BACKGROUND: Brain metastases (BM) are the most common central nervous system tumor in the United States and occur with increasingly frequency due to improved screening and therapeutics leading to improved survival. Current estimates of frequency of BM vary significantly by cancer site and are typically not population-based. Population-based estimates of incidence have recently become possible due to collection of data on BM identified at diagnosis (“synchronous” BM, SBM). BM may occur at any point after cancer diagnosis. We report our recent population-based estimates of SBM and period incidence of BM (PBM) from breast (BC) and lung cancer (LC). METHODS: Data from Surveillance, Epidemiology, and End Results (SEER, 2010–2016 diagnoses) were used to estimate SBM and linked data from SEER-Medicare (2008–2012 diagnoses for individuals 65+, with 2007–2014 claims) were used to estimate PBM, for BC and LC overall and by BC and LC subtypes. RESULTS: Within the SEER data, 10.9% of LC cases presented with SBM (15.5% in small cell LC [SCLC], and 10.8% in non-small cell LC [NSCLC]); 0.4% of BC cases presented with SBM, 0.7% in triple negative (TNBC), 0.8% for HER2+, and 0.2% for ER+\PR+\HER2-. Within the SEER-Medicare data, 13.5% of LC overall had LBM with 23.1% for SCLC and 15.3% for NSCLC; 1.8% of BC overall had LBM with 4.2% in triple negative (TNBC), 3.1% for HER2+, and 1.1% for ER+\PR+\HER2. CONCLUSION: Frequency of synchronous and period BM varies by originating site as well as subtype. The new SBM variable in SEER allows for estimation of this important statistic, while the SEER-Medicare linked data allows for estimation of PBM, both on a population-level for the US population. These estimates are useful to clinical practice and critical for estimating morbidity and mortality due to BM.